Peran Kegiatan Keagamaan Dalam Membentuk Karakter Remaja di Masjid Nurul Huda Desa Jentrek Wonosobo - Naili Salsabila; Sri Haryanto; Salis Irvan Fuadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The main objective of this research is to determine the types of religious activities that take place at the Nurul Huda Mosque, Jentrek Village. (2) To find out how religious activities at the Nurul Huda Mosque, Jentrek Village, Wonosobo, influence the character of teenagers. (3) To find out what influences and hinders religious involvement in forming the moral fiber of teenagers at the Nurul Huda Mosque, Jentrek Village, Wonosobo.Qualitative research methodology was used in this investigation. Descriptive qualitative methodology is the strategy used. Through observation, documentation and interviews, data was collected. Technical and source triangulation is used to assess the veracity of the data.In this research, conclusions were obtained The forms of religious activities at the Nurul Huda Mosque in Jentrek Village are Routine Mujahadah and Majlis taklim. Meanwhile, the aim of holding mujahadah activities and taklim assemblies is of course to shape the character of teenagers to be better, especially in terms of religious character, social awareness and responsibility. The role of religious activities in forming the character of teenagers at the Nurul Huda Mosque. Starting from the activities of reading tahlil, wirid and prayers, this adds to the religious value of teenagers by becoming more attentive to each other, such as reminding each other and embracing each other, this shows that their sense of concern has grown slowly without them realizing it. Through taklim meetings and mujahadah events, teenagers can understand their responsibilities towards the Creator. As evidenced by these actions, a sense of obligation as a human being in the world begins to form, namely obeying the commands of Allah SWT and staying away from His prohibitions. Aspects of encouraging and inhibiting religious activities at the Nurul Huda Mosque in shaping the character of the younger generation. Motivational elements include personal interests, societal norms, and parental beliefs. Meanwhile, age, education and boredom are inhibiting factors.